2021
DOI: 10.3389/fonc.2021.738330
|View full text |Cite
|
Sign up to set email alerts
|

Non-Mass Enhancements on DCE-MRI: Development and Validation of a Radiomics-Based Signature for Breast Cancer Diagnoses

Abstract: PurposeWe aimed to assess the additional value of a radiomics-based signature for distinguishing between benign and malignant non-mass enhancement lesions (NMEs) on dynamic contrast-enhanced breast magnetic resonance imaging (breast DCE-MRI).MethodsIn this retrospective study, 232 patients with 247 histopathologically confirmed NMEs (malignant: 191; benign: 56) were enrolled from December 2017 to October 2020 as a primary cohort to develop the discriminative models. Radiomic features were extracted from one po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 32 publications
(41 reference statements)
0
9
0
Order By: Relevance
“…radiomics signature and clinicopathological variables (including SWE) could preoperatively predict the Ki-67 expression level in BC patients with a satisfactory performance. Radiomics has shown a great capability in differentiating benign and malignant tumors (20, 21, 30), discriminating molecular subtypes (31), distinguishing between benign and malignant non-mass enhancement lesions (32), predicting ALN metastasis (24,33) (35,36), this study, on the one hand, adopted a more convenient and economical ultrasound imaging means, while also taking into account the hardness assessment of shear wave elastography; on the other hand, the training and validation sets achieved AUC values of 0.904 and 0.890, with better diagnostic performance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…radiomics signature and clinicopathological variables (including SWE) could preoperatively predict the Ki-67 expression level in BC patients with a satisfactory performance. Radiomics has shown a great capability in differentiating benign and malignant tumors (20, 21, 30), discriminating molecular subtypes (31), distinguishing between benign and malignant non-mass enhancement lesions (32), predicting ALN metastasis (24,33) (35,36), this study, on the one hand, adopted a more convenient and economical ultrasound imaging means, while also taking into account the hardness assessment of shear wave elastography; on the other hand, the training and validation sets achieved AUC values of 0.904 and 0.890, with better diagnostic performance.…”
Section: Discussionmentioning
confidence: 99%
“…Radiomics has shown a great capability in differentiating benign and malignant tumors ( 20 , 21 , 30 ), discriminating molecular subtypes ( 31 ), distinguishing between benign and malignant non-mass enhancement lesions ( 32 ), predicting ALN metastasis ( 24 , 33 ), and responding to neoadjuvant chemotherapy ( 34 ) based on MRI, CT or US findings. A recent research showed that MRI- or digital breast tomosynthesis-based radiomics can be used for prediction of Ki-67 expression level in BC patients.…”
Section: Discussionmentioning
confidence: 99%
“…This study reviewed 4,519 consecutive patients who underwent breast DCE-MRI in our hospital between December 2017 and November 2021 (including the patients examined between December 2017 and April 2021 described in our previous study). As previously reported ( 9 ), the inclusion criteria included (I) lesions presenting as NMEs in DCE-MRI images, (II) complete clinical and pathological data, (III) the absence of lactation or pregnancy, and (IV) the absence of breast implants or previous treatments. Lesions with (I) maximal a diameter less than 5 mm, (II) apparent hemorrhage after biopsy, and (III) poor image quality were excluded.…”
Section: Methodsmentioning
confidence: 99%
“…All MR images were obtained using the protocols described in our previous study ( 9 ). The imaging parameters for the multi-b value DWI with readout-segmented echo-planar imaging (RESOLVE DWI) sequence was as follows: repetition time (TR) =5,000 ms; echo time (TE) =70 ms; field of view (FOV) =169×280 mm 2 ; matrix size =114×188; slice thickness =5.0 mm; readout segment =5, average =1; diffusion gradient mode =3-scan trace; and b values =0, 50, and 1,000 s/mm 2 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation